Complying with Sharia While Exempting from Value-Added Tax: Murābaḥah in Indonesian Islamic Banks - Nur Hidayah; Moch. Bukhori Muslim; Abdul Azis (Universitas Islam Negeri Jakarta, 2022)
Law number 42/2009 on Value Added Tax and some subsequent amendments have exempted Islamic banks from the value-added tax on their murābaḥah transactions. This provision raises the sharia issue because the goods are delivered directly from the supplier to the customer. At the same time, the DSN-MUI Fatwa regarding the murābaḥah contract sets that banks must first buy and own the goods from the suppliers before selling them back to the customers. With this tax provision, murābaḥah transactions have shifted from trade systems to service ones because banks directly transfer funds to customers to purchase goods. Such tax policy has dealt with the so-called double taxation issue of Islamic banks but sacrificed the compliance of sharia principles. This paper seeks to solve this dilemma by proposing a revision of tax regulations for murābaḥah transactions using philosophical, juridical, and sociological legal approaches. The delivery of goods from suppliers to banks and from banks to customers is included in non-taxable goods transactions for Islamic banks. With this proposal, Islamic banks are expected to be exempted from value-added tax while complying with sharia principles and competing with conventional banks. AbstrakUU No. 42/2009 tentang Pajak Pertambahan Nilai dan beberapa amandemen berikutnya telah membebaskan bank syariah dari pajak pertambahan nilai (PPN) pada transaksi murabahah. Namun ketentuan ini dianggap menimbulkan isu syariah karena barang diserahkan langsung dari pemasok ke nasabah, sedangkan Fatwa DSN-MUI tentang akad murabahah mengatur bahwa bank harus membeli dan memiliki barang terlebih dahulu dari pemasok sebelum menjualnya kembali kepada nasabah. Dengan ketentuan pajak ini, transaksi murabahah telah bergeser dari sistem jual beli menjadi sistem jasa karena bank dianggap tidak melakukan pembelian barang melainkan mentransfer dana pembelian barang kepada nasabah. Ketentuan pajak ini telah meringankan beban pajak pertambahan nilai bank syariah namun mengorbankan pemenuhan prinsip syariah. Kajian ini berupaya mencari solusi dilema ini dengan usulan revisi regulasi perpajakan untuk transaksi murabahah dengan pendekatan analisa legal filosofis, normatif, dan sosiologis. Penyerahan barang dari pemasok kepada bank dan dari bank kepada nasabah dimasukkan dalam transaksi barang tidak kena pajak. Dengan usulan ini diharapkan bank syariah tetap terhindar dari pajak ganda, namun tetap memenuhi prinsip syariah serta berdaya saing dengan bank konvensional.